Rancang Bangun Sistem Informasi Kelola Absensi dengan Sidik Jari Berbasis Web di PT Kewalram Indonesia - Sri Yulianti; Nano Suyatna; An-Nisa Aina Nurwaida (Jurnal Dimamu, 2022)
Attendance is a data collection to determine the number of employee attendance at a company or agency. Attendance is evidence of attendance data that is very important to provide reports to superiors. The procedure used is still using a manual system where there is a risk of fraud when doing attendance and losing data so that currently a good system is needed. PT Kewalram Indonesia Designs and Builds a very Modern Employee Attendance Information System, namely Using WEB-Based Fingerprints is a system created to solve problems in the personnel department, especially attendance problems at PT Kewalram Indonesia. The system development method used is the RUP (Rational Unified Process) model. ) with OOAD (Object Oriented Analysis and Design) where the developer tool is UML (Unified Modeling Language). As for the system design, it is equipped with use case diagrams, sequence diagrams, activity diagrams and class diagrams. The purpose of designing this system is to simplify the attendance process, input and store attendance data and make it easier to find attendance data.